The bio-sensing performance and electrochemical properties of non-carbonised electrospun nanofibers: article - Tahal@Tahar, Noor Hafizah; Tan, Huey Ling (2019)
In this study, there are four samples based on Poly (Acrylic Acid) (PAA) and Polyacrylonitrile (PAN) (PAA/PAN) polymer. The sample with only PAA/PAN act as bare which not included with any other materials. The other three samples were mixed with different types of material which is Gold Nanoparticles (AuNPs), reduced Graphene Oxide (rGO) and Iron(III)Oxide (Fe₂O₃). Firstly, the PAA/PAN based polymer solution undergo electrospinning process producing PAA/PAN, PAA/PAN/AuNPs, PAA/PAN/rGO and PAA/PAN/Fe₂O₃ nanofibers. The nanofibers then being analyzed by Cyclic Voltammetry (CV) to check whether there is any redox reaction takes place on the nanofibers and to study the electrochemical properties of the nanofibers. It was found that PAA/PAN/rGO nanofibers showed the best biosensing performance followed by PAA/PAN, PAA/PAN/AuNPs and PAA/PAN/Fe₂O₃ due to electrochemical properties shown by the obtained data. Both concentration dependence study and scan rate dependence study showed PAA/PAN/rGO nanofibers have the highest current detection and highest redox reaction, respectively. Besides, Electrochemical Impedance Spectroscopy (EIS) analysis was conducted to check the conductivity of the nanofibers. From the EIS analysis, it showed that PAA/PAN/AuNPs nanofibers have the highest conductivity compared to others. The objectives of this study was achieved.